Biomechanical evaluation of lumbar spondylolysis repair with various fixation options: A finite element analysis - Ye, Yuchen; Jin, Shichang; Zou, Yang; Fang, Yuekun; Xu, Panpan; Zhang, Zhili; Wu, Nan; Zhang, Changchun (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: This study was designed to compare the biomechanical properties of lumbar spondylolysis repairs using different fixation methods by using three-dimensional finite element analysis. Methods: Five finite element models (A, B, C, D, and E) of L4-S1 vertebral body were reconstructed by CT images of a male patient (A: intact model; B: spondylolysis model; C: spondylolysis model with intrasegmental direct fixation by Buck screw; D: spondylolysis model with intersegmental indirect fixation by pedicle screw system; E: spondylolysis model with hybrid internal fixation). L5-S1 level was defined as the operative level. After the intact model was verified, six physiological motion states were simulated by applying 500N concentrated force and 10Nm torque on the upper surface of L4. The biomechanical properties of the three different internal fixation methods were evaluated by comparing the range of motion (ROM), maximum stress, and maximum displacement. Results: Compared with Model B, the ROM and maximum displacement of Model C, D, and E decreased. The maximum stress on L5/S1 disc in models A, B, and C was much higher than that in Model D and E under extension and lateral bending conditions. Under axial rotation and lateral bending conditions, the maximum stress of interarticular muscle and internal fixation system in Model B and Model C was significantly higher than that in Model D and Model E. In contrast to Model D, the stress in Model E was distributed in two internal fixation systems. Conclusion: In several mechanical comparisons, hybrid fixation had better biomechanical properties than other fixation methods. The experimental results show that hybrid fixation can stabilize the isthmus and reduce intervertebral disc stress, which making it the preferred treatment for lumbar spondylolysis.